The circ_0021977/miR‐10b‐5p/P21 and P53 regulatory axis suppresses proliferation, migration, and invasion in colorectal cancer. Issue 3 (8th October 2019) - Lu, Chen; Jiang, Wei; Hui, Bingqing; Rong, Dawei; Fu, Kai; Dong, Chaoxi; Tang, Weiwei; Cao, Hongyong
Abstract: An in‐depth understanding of circular RNAs (circRNAs) indicates that they are abundant in the eukaryotic transcriptome. Many circRNAs act as microRNA sponges; thus, they represent a new type of regulatory factor. However, the role of circRNA in colorectal cancer (CRC) remains largely unknown. Low circ_0021977 expression in patients with CRC is associated with higher tug‐lymph node metastasis (TNM) stage and poorer prognosis compared with patients with high circ_0021977 expression. Moreover, miR‐10b‐5p was shown to be a target of circ_0021977, and p21 and p53 are suggested to be putative target genes of miR‐10b‐5p. The results showed that the circ_0021977/miR‐10b‐5p/p21&p53 regulatory axis suppresses proliferation, migration, and invasion by CRC cells. This evidence reveals new relationships and brings new highlights to the treatment of CRC. Abstract : The circ_0021977/miR‐10b‐5p/p21 and p53 regulatory axis suppresses the proliferation, migration, and invasion in CRC cells. This evidence have revealed new attraction and bring a new light to the treatment of CRC.